Expectations and Standards for Accounting Professions and Implications in the Learning Pattern in Industrial 4.0 - Iman Supriadi; Miya Dewi Suprihandari; Kusuma Adi Rahardjo (Yayasan Ilomata, 2020)
This paper talks about the impact from the commercial transformation 4.0 on accounting scientific research and accounting education and learning patterns. The commercial transformation can be turbulent and make development throughout accounting scientific research and designs from accounting knowing or education and learning in the future. To ensure that the adjustment needs from accounting professionals and trainees that are taking accounting research studies are required to have the ability to instantly adapt to the instructions from modifications in market 4.0 that are currently operating. It‘s anticipated that accounting will modification to